Mentoring in a Cooperative Learning Classroom - Jacqueline Gilbert (Georgia Southern University, 2021)
This manuscript introduces an experiential model of cooperative learning, and a public/private partnership between industry and higher education—one that included mentors as an integral part of the classroom experience. Each of thirty-seven students in a Principles of Management Experiential Learning class was assigned an experienced executive/professional who served as their mentor. These individuals had experience congruent with students’ career goals and aspirations, and they were able to help them craft a reflective end-of-term paper. Interview data from mentors illustrates the type of career guidance and advice they offered to their mentees, and why they thought that mentoring was important for college students. Because academic research has demonstrated the benefits of mentoring for both mentors and mentees alike, this paper argues for modifying the performance appraisal system within higher education so that mentoring can become a standard part of the student and faculty experience.